PIGEON PEA SEED: LEVEL OF AWARENESS, UTILIZATION AND CONSTRAINTS TO USE AS A FEEDSTUFF AMONG LIVESTOCK FARMERS IN OGBOMOSO ZONE OF NIGERIA - Janet Temitope OJEDIRAN; Taiwo Kayode OJEDIRAN; Shakirat SALAMI; Victor DUROJAIYE; Rasheed Gbolagade ADEOLA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Livestock farmers (n=253) from five local government areas of Ogbomoso, Southwest Nigeria were interviewed through a well-constructed questionnaire. This study assessed the demographic characteristics of the livestock farmers, type of livestock kept, type of feed used, energy and plant protein feedstuffs used in feed compounding, level of awareness of pigeon pea seed utilization as livestock feedstuff and constraints to the use of pigeon pea seed as livestock feedstuff. The survey results revealed that the respondents were mostly part time livestock farmers, married-middle aged men (𝑥̅=40 years) with an average 5 years farming experience, who kept majorly poultry and pigs (55-80%) amongst other livestock. Compounded rations (53-83%) were commonly used with maize (66-100%) as the main energy feedstuff while soybean meal (87-90%), groundnut cake (77-100%) and palm kernel cake (86- 92%) were the major plant protein ingredients. Majority of the respondents (70-82%) were unaware of the potential use of pigeon pea seed as livestock feedstuff but those that were aware indicated that antinutrients and or processing (88-100%) were the serious concern for use as a feedstuff. It can therefore be recommended that agricultural extensionists should work together with livestock nutritionists and re-orient the farmers with available research outputs that have addressed this constraint.